Piezoelectric system with software management - Fandiño Gómez, Jayr Antonio; Cortes López, Segundo Leonardo; Valderrama García, Leonardo (Ingeniería Solidaria, 2023)
This article is a product of the project "Piezoelectric system with software management", developed by Jayr Antonio Fandiño Gómez in conjunction with the University of Cundinamarca Ubaté sectional. Objective: To develop a source of clean energy with the help of piezoelectric materials, to take advantage of the passage of people within the University of Cundinamarca, Ubaté sectional, generating savings of "energy" resources. Method: Different phases have been carried out using different sensors in order to create a better product which is capable of generating clean energy that can be used for the lighting supply of this public space. Results: A piezoelectric tablet of large dimensions and optimized has been created, which was implemented for testing within the University of Cundinamarca, Ubaté sectional generating results that led to the creation of a NoSQL database. Conclusion: By implementing a new renewable energy system in an area where there are environmental concerns, awareness of the different problems generated by the advancement of technology will be generated. Limitation of the study: The acquisition of the sensors can be complicated due to the fact that this product is mostly created abroad.